Disparities in Temporal and Geographic Patterns of Declining Heart Disease Mortality by Race and Sex in the United States, 1973–2010. Issue 12 (15th December 2015) - Vaughan, Adam S.; Quick, Harrison; Pathak, Elizabeth B.; Kramer, Michael R.; Casper, Michele
Abstract : Background: Examining small‐area differences in the strength of declining heart disease mortality by race and sex provides important context for current racial and geographic disparities and identifies localities that could benefit from targeted interventions. We identified and described temporal trends in declining county‐level heart disease mortality by race, sex, and geography between 1973 and 2010. Methods and Results: Using a Bayesian hierarchical model, we estimated age‐adjusted mortality with diseases of the heart listed as the underlying cause for 3099 counties. County‐level percentage declines were calculated by race and sex for 3 time periods (1973–1985, 1986–1997, 1998–2010). Strong declines were statistically faster or no different than the total national decline in that time period. We observed county‐level race–sex disparities in heart disease mortality trends. Continual (from 1973 to 2010) strong declines occurred in 73.2%, 44.6%, 15.5%, and 17.3% of counties for white men, white women, black men, and black women, respectively. Delayed (1998–2010) strong declines occurred in 15.4%, 42.0%, 75.5%, and 76.6% of counties for white men, white women, black men, and black women, respectively. Counties with the weakest patterns of decline were concentrated in the South. Conclusions: Since 1973, heart disease mortality has declined substantially for these race–sex groups. Patterns of decline differed by race and geography, reflecting potential disparities in national and local drivers of these declines. Better understanding of racial and geographic disparities in the diffusion of heart disease prevention and treatment may allow us to find clues to progress toward racial and geographic equity in heart disease mortality.